1972
DOI: 10.1111/j.1365-2362.1972.tb00676.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Triglyceride and Fatty Acid Metabolism in Diabetes mellitus

Abstract: Abstract. Free fatty acid and triglyceride metabolism was studied in diet‐responsive and insulin‐dependent diabetics and in non‐diabetic obese patients before and during treatment. Free fatty acid turnover was elevated in diabetics and in most obese patients, and was decreased by diabetic control; it showed no significant change in the obese patients during caloric restriction. Plasma triglyceride levels exceeded 160 mg/100 ml in 20 of the 34 diabetics, and gross lipaemia occurred both in insulin‐requiring an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 49 publications
5
28
0
Order By: Relevance
“…However, reduced triglyceride synthesis in more chronic insulin deficiency, whether a primary or secondary effect, must inevitably reduce VLDL triglyceride secretion. The reduction in serum triglyceride when insulin is administered to patients with either type I or type II diabetes (52) and primary hypertriglyceridemia (53,54) is consistent with an inhibitory effect of insulin on triglyceride secretion, although a major contribution to this effect may be the reduction in serum free fatty acid levels or effects on lipoprotein lipase levels.…”
Section: Discussionmentioning
confidence: 92%
“…However, reduced triglyceride synthesis in more chronic insulin deficiency, whether a primary or secondary effect, must inevitably reduce VLDL triglyceride secretion. The reduction in serum triglyceride when insulin is administered to patients with either type I or type II diabetes (52) and primary hypertriglyceridemia (53,54) is consistent with an inhibitory effect of insulin on triglyceride secretion, although a major contribution to this effect may be the reduction in serum free fatty acid levels or effects on lipoprotein lipase levels.…”
Section: Discussionmentioning
confidence: 92%
“…The abnormalities in serum lipoprotein pattern of insulin-deficient diabetic patients are partly accounted for by the decrease of tissue LPL activity. Thus, it is likely that the increase of VLDL and probably also the increase of LDL-triglyceride is caused by impaired removal of triglyceride from these particles at peripheral tissues even though an increase in splanchnic production of VLDL may also be present and contribute to the rise of triglycerides [4][5][6]. The decrease of HDL-cholesterol could also be related to the LPL deficiency and to concomitant reduction in the plasma clearance of triglyceride-rich lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic analyses have suggested that the increase of triglyceride and VLDL concentrations in uncontrolled insulin-dependent diabetes is chiefly accounted for by a combination of increased splanchnic production of triglycerides and their inefficient removal [4,5]. The defect in removal of VLDL triglycerides has been attributed to low activity of lipoprotein lipase (LPL), and, indeed, clearly decreased LPL activities have been demonstrated in postheparin plasma of untreated juvenile diabetic patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…Reaven and Reaven [36] come to a similar conclusion in studies on the development of hypertriglyceridaemia in acute and chronic streptozotocin-diabetic rats. In diabetic patients, Lewis et al [37] noted the importance of reduced extra-hepatic catabolism in controlling VLDL levels. In support of this, a reduction in lipoprotein lipase activity has been observed in insulin-deficient diabetes mellitus [3840] as well as a defect in VLDL removal [41].…”
Section: Discussionmentioning
confidence: 99%